(untitled) (Revista LIDER, 2020)
The maturity of the tragedy of the Commons means that the irreversibility of degradation and destruction of what we share as Humanity, has reached dimensions of immediacy and concretion never before achieved. Stronger since the 1960s, the scientific legitimacy of the need to control and manage the common has been joined by its social legitimacy. The discussion about what is at the base of the tragedy is shared by various approaches: if it is a demographic issue, or technological or political ones, among others. The answer appears to be a radical change in the styles of development and living, rather than reducing the number of people is needed a more effective distribution of the fruits of evolution, based on values shared by all the human beings, and where the right to life of present and future generations takes precedence above any other. The difficulties of global consensus do not justify the local immobility. Within our time and vital space, we still have sufficient degrees of freedom to disable those “small” tragedies of our daily life. The path might be indicated by what is called Integral Development, our contribution from below to global thoughts and actions.